Elastomeric and Dynamic MnO2/CNT Core–Shell Structure Coiled Yarn Supercapacitor. Issue 5 (11th January 2016) - Choi, Changsoon; Sim, Hyeon Jun; Spinks, Geoffrey M.; Lepró, Xavier; Baughman, Ray H.; Kim, Seon Jeong
Abstract : Reversibly deformable and highly performing solid‐state yarn supercapacitors are obtained using MnO2 ‐deposited microcoiled yarn electrodes. The core(CNT)–shell(MnO2 )‐structured coiled electrodes achieve high stretchability (37.5%) without the help of elastomeric substrates, minimizing the size of the supercapacitors. Therefore, high specific capacitances of 34.6 F cm −3, 61.25 mF cm −2, and 2.72 mF cm −1 are achieved for coiled supercapacitors without impairing mechanical stretchability or electrochemical cyclability.